2007
DOI: 10.1172/jci30575
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the signaling molecule CalDAG-GEFI represent a model for leukocyte adhesion deficiency type III

Abstract: Single gene mutations in β integrins can account for functional defects of individual cells of the hematopoietic system. In humans, mutations in β 2 integrin lead to leukocyte adhesion deficiency (LAD) syndrome and mutations in β 3 integrin cause the bleeding disorder Glanzmann thrombasthenia. However, multiple defects in blood cells involving various β integrins (β 1 , β 2 , and β 3 ) occur simultaneously in patients with the recently described LAD type III (LAD-III). Here we show that the product of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 57 publications
6
175
1
Order By: Relevance
“…GTPases in turn are activated by guanine nucleotide exchange factors (GEFs). In neutrophils stimulated with leukotriene B 4 , Rap1 is activated by CalDAG-GEFI, which is activated by Ca 2+ and DAG, two products of PLC (39). In contrast, another study using fMLP stimulation revealed that the GEFs Vav1 and PRex1 redundantly mediate the activity of the GTPase Rac (40), suggesting that the different stimuli activate distinctly different pathways.…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…GTPases in turn are activated by guanine nucleotide exchange factors (GEFs). In neutrophils stimulated with leukotriene B 4 , Rap1 is activated by CalDAG-GEFI, which is activated by Ca 2+ and DAG, two products of PLC (39). In contrast, another study using fMLP stimulation revealed that the GEFs Vav1 and PRex1 redundantly mediate the activity of the GTPase Rac (40), suggesting that the different stimuli activate distinctly different pathways.…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…2). Rasgrp2 -/-mice have impaired integrinmediated adhesion in platelets and neutrophils and are considered to be a model for human LAD-III (Bergmeier et al, 2007;Crittenden et al, 2004). This might be so because several LAD-III patients have a mutation in CalDAG-GEF1 that has been reported to affect splicing (Pasvolsky et al, 2007).…”
Section: Activation Of Integrins By Inside-out Signallingmentioning
confidence: 99%
“…Both talin and kindlin-3 have similar FERM (protein 4.1, ezrin, radixin and moesin) domains that bind the β-subunit of integrins at the two NPxY sites (in which x denotes any amino acid) -talin at the membrane-proximal site and kindlin-3 at the membrane-distal site (Ma et al, 2008;Moser et al, 2008). Kindlin-3 knockout (Fermt3 -/-) mice have severe bleeding problems (Moser et al, 2008) similar to the Rasgrp2 -/-mice (Bergmeier et al, 2007;Crittenden et al, 2004), suggesting that kindlin-3 is also a candidate gene involved in LAD-III.…”
Section: +mentioning
confidence: 99%
“…Rap isoforms regulate adhesion-dependent processes by modulating integrin affinity and avidity. 2 Loss of leukocyte Rap1 activation is a cause of LAD-III, 3,4 demonstrating the crucial role of this small GTPase in neutrophil control. Agonist-activated PI3Ks generate on activation the lipid second messengers phosphatidylinositol-(3,4,5)-trisphosphate [PtdIns(3,4,5)P 3 ] and PtdIns(3,4)P 2 .…”
mentioning
confidence: 99%